2008
DOI: 10.1590/s0036-46652008000500004
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of five extracellular enzymes by strains of chromoblastomycosis agents

Abstract: SuMMaryThe gelatinase, urease, lipase, phospholipase and DNase activities of 11 chromoblastomycosis agents constituted by strains of Fonsecaea pedrosoi, F. compacta, Phialophora verrucosa, Cladosporium carrionii, Cladophialophora bantiana and Exophiala jeanselmei were analyzed and compared. All strains presented urease, gelatinase and lipase activity. Phospholipase activity was detected only on five of six strains of F. pedrosoi. DNase activity was not detected on the strains studied. Our results indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
(32 reference statements)
1
7
0
1
Order By: Relevance
“…In this study, proteinase activity was observed in 1.8% of the environmental Exophiala isolates and in none of the clinical isolates. Consistent with our findings, phospholipase activity was not detected in a strain of E. jeanselmei from case of human chromoblastomycosis . However, Gugnani and Okeke evaluated 39 environmental dematiaceous opportunists and found positive phospholipase activity in two E. jeanselmei isolates.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, proteinase activity was observed in 1.8% of the environmental Exophiala isolates and in none of the clinical isolates. Consistent with our findings, phospholipase activity was not detected in a strain of E. jeanselmei from case of human chromoblastomycosis . However, Gugnani and Okeke evaluated 39 environmental dematiaceous opportunists and found positive phospholipase activity in two E. jeanselmei isolates.…”
Section: Discussionsupporting
confidence: 89%
“…DNases may enhance evasion of the innate immune response . DNase activity proved to be absent from E. jeanselmei . In our study, the enzyme was rarely found among the isolates tested, being limited to the most common opportunist, genotype A of E .…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…LOD: limit of detection Note the diversity of conidium shape and size, ranging from short ellipsoid to more-or-less triangular to long ellipsoid (arrow) eased fish cannot be separated from isolates ob tained from other substrates such as wood and water, at least not with the currently used genetic marker, it is likely that E. angulospora is an opportunistic pathogen not restricted to a pathogenic life history. Species of Exophiala are known to produce a variety of extracellular en zymes, including ureases, gelatinases, and lipases (De Souza et al 2008, Corbellini et al 2009). Effects of extracellular enzymes on fish host cells may explain why dead cells were observed in layer 1 of the foci where abundant fungal hyphae were present, but not in the layers containing few hyphae.…”
Section: Discussionmentioning
confidence: 99%
“…Necrotizing extracellular enzymes released by the fungus may be a contributing factor as well (de Souza et al . ). Fungal melanin likely plays a protective role in the environment and serves as a virulence factor, providing protection from the effects of hydrolytic enzymes and free radicals produced by phagocytes (Revankar & Sutton ).…”
mentioning
confidence: 97%